ประสบการณ์การเป็นพยาบาลที่ปฏิบัติงานหน่วยงานอุบัติเหตุและฉุกเฉินในยุคใหม่ โรงพยาบาลทั่วไปแห่งหนึ่ง - ดุสิต กล่ำถึก (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The purpose of the qualitative study is to describe experience of being a nurse working in a new era emergency unit at a general hospital. Hermeneutic phenomenology of Martin Heidegger was applied as research methodology. Purposive sampling was used to select 12 nurses who working in Emergency unit. The in-depth interview with tape- record and observation. All interviews were transcribed verbatim and analyzed by using content analysis of Crist and Tanner. The findings regarding to this study were consisted of 4 major themes as follows:1. Background and Preparedness in Working in the ER including the following sub-themes: 1.1) Various reasons for working in the ER , 1.2) Starting work with feeling in-confident and needing time to adjust and 1.3)  Preparation of knowledge for patient care.2. Responsibilities of Nurses working in the ER including the following sub-themes: 2.1) Screening patients requires various skills, 2.2) Monitoring patients in observation room, 2.3) Assisting in resuscitation by following correct technique, 2.4) Providing patient referral services, 2.5) Working with Emergency medical service, 2.6) Engaging in public services during disasters and emerging epidemics and 2.7) Providing community education services.3. Work-related issues managed by the in-charge nurse including the following sub-themes: 3.1) Managing appropriate staffing when crowded with patients, 3.2) Communicating with patients and their families about prolonged wait times, 3.3) Preventing care errors through verification and validation processes and 3.4)  Resolving chaotic situations through collaborative efforts.4. Results of working in an ER including the following sub-themes: 4.1) Stress from management in the modern workplace, 4.2) Struggling to balance personal life and demanding work and 4.3) Happiness comes from good teamwork and ensuring patient safety.This research provides an understanding of working as a nurse in the Emergency Room (ER) and emphasizes the care and management of patients who enter the unit. It also addresses the challenges and managerial approaches that nurse administrators can use to develop both individuals and the ER unit.